Evaluation of calcium lignosulfonate as a acceptable previous cargo for edible fats and oils. (23rd December 2019) - ,; Schrenk, Dieter; Bignami, Margherita; Bodin, Laurent; Chipman, James Kevin; del Mazo, Jesús; Grasl‐Kraupp, Bettina; Hogstrand, Christer; Hoogenboom, Laurentius (Ron); Leblanc, Jean‐Charles; Nebbia, Carlo Stefano; Nielsen, Elsa; et al.
Abstract: Shipping of edible fats and oils into Europe is permitted in bulk tanks, provided that the previous cargo is included in a positive list. The European Commission requested EFSA to evaluate the acceptability of calcium lignosulfonate as previous cargo for fats and oils. The evaluation was based on the same criteria as those used for the evaluation of the substances currently on the list in the Annex to Commission Directive 96/3/EC as a acceptable previous cargoes for edible fats and oils. In 2017, the EFSA Panel on Contaminants in the Food Chain (CONTAM Panel) concluded that calcium lignosulfonate did not meet the acceptability criteria, due to uncertainties as regards the composition and toxicity of its low‐molecular weight fraction (LMWF) below 1, 000 Da. In the current evaluation, new information, showing lack of genotoxicity of the LMWF isolated from a technical grade of calcium lignosulfonate was provided. Due to uncertainties regarding the presence of lignosulfonate components below 200 Da in this LMWF tested for genotoxicity, the CONTAM Panel concluded that the information provided was insufficient to assess the acceptability of calcium lignosulfonate as previous cargo. The Panel recommends a better analysis of the LMWF and a new genotoxicity test using this LMWF, including components < 200 Da, and evidence that the tested material is representative of the LMWF in products intended to be shipped as previous cargo for edible fat and oils.